Portrait of Islamic Religious Education Teachers in Educating Students in the Digital Era - Muhammad Azka Hafidzi; Dwi Istiyani (JIE (Journal of Islamic Education), 2026)
This research aims to describe the portrait of Islamic Religious Education (IRE) teachers in educating students in the digital era, particularly in relation to their roles, strategies, and challenges they face. This study employs a qualitative approach with a case study design, collecting data through semi-structured interviews with three IRE teachers, observation of learning in grades I–VI, and documentation of activities and school records. The validity of the data is guaranteed through triangulation of sources and techniques, while the analysis is carried out using the Miles, Huberman, and Saldana models through reduction, presentation, and conclusion drawn. The results of the study show that IRE teachers carry out complex roles, including instilling digital morals, guiding religious literacy, being role models in the use of technology, motivating students, and evaluating understanding through digital media. The strategies implemented include the use of digital teaching materials, such as videos, images, and animations; interactive and contextual learning methods; digital communication with parents; and teacher competency development. The weakness of this study lies in the limited number of informants and also only conducted in one school.